A common polymorphism in the human immunoreceptor NKp65 determines ligand interaction, cell surface expression and function - Julian Leonard Lino Heller; Yvonne Bartel; Catalin Schach; Angelina Kirsten; Felicitas Schlatter; Alexander Steinle (PLoS ONE, 2025)
Background The human immunoreceptor NKp65 is specifically expressed by a subset of human innate lymphocytes, i.e., innate lymphoid cells group 3 (ILC3) and activates cellular cytotoxicity upon interaction with its genetically linked ligand KACL. In the context of the present study, the relevance of a common polymorphism in the NKp65-coding KLRF2 gene was addressed. Methods Using biophysical methods such as flow cytometry and surface resonance spectroscopy, as well as immunological methods such as ELISA and immunoblots and cytotoxicity assays, the influence of polymorphism rs576601 on surface expression, binding kinetics to the ligand KACL, proteolytic cleavage, intracellular retention, and functional responsiveness of NKp65 was investigated. Results Polymorphism rs576601 entails the exchange of cytosine for adenine, resulting in a substitution of proline by threonine at amino acid position 131 within the C-type lectin-like ectodomain of NKp65. Here, we show that the NKp65-Thr131 variant is only weakly expressed on the cell surface as compared to the NKp65-Pro131 variant. This is due to an enhanced intracellular retention of NKp65-Thr131 but not due to proteolytic cleavage. In addition, the polymorphism rs576601 has a significant impact on the binding kinetics and affinity to the ligand KACL. On a functional level, the combination of reduced surface expression and affinity resulted in a drastically reduced cellular cytotoxicity of NKp65-Thr131+ effector cells towards KACL+ target cells. Conclusions The polymorphism rs576601 affects ligand interaction, cell surface expression and function of NKp65. Since the NKp65 ligand KACL is primarily expressed on keratinocytes, polymorphism rs576601 may impact on skin immunosurveillance by NKp65-expressing ILC3.